Who Builds Audience Loyalty Better? Comparing the Influence of Communication Style and Credibility Between Human and AI Presenters - Surianto Surianto; Hendyawan Theo (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the influence of communication style and source credibility of human and Artificial Intelligence (AI) presenters on audience loyalty toward the Apa Kabar Indonesia program on tvOne. This research employed a quantitative approach with a positivist paradigm using a survey method. Data were collected through questionnaires distributed to 100 respondents who had watched both the human presenter, Kamaratih Kusuma, and the AI presenter, Nadira. The findings indicate that communication style and source credibility significantly affect audience loyalty both partially and simultaneously. Human presenters are perceived to have stronger emotional connections and more natural communication delivery, while AI presenters demonstrate greater consistency and efficiency in conveying information. The coefficient of determination shows that the communication style and credibility of the human presenter contribute 73.00% to audience loyalty, while AI Presenter contribute 79,4% to audience loyalty. The study concludes that although AI technology offers innovation in television broadcasting, human elements such as emotional engagement and communication style remain essential in maintaining audience loyalty. However, human presenter needs other factors to enhance their performance on audience loyalty. This research contributes to communication and broadcasting studies regarding the integration of AI technology in television news media.